Pencapaian Cakupan Imunisasi - Surahma Asti Mulasari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Immunization is an effort to improve a person's immune to a disease. The purpose of immunization is to stimulate the immunological system of the body to develop antibodies (immune) specific, so that it can protect the body from a disease Preventable Diseases by Immunization (PD3I).Objective: The aim of this study was to know the immunization coverage rate in Pedukuhan Sembuh Wetan Sidokarto Godean 2012.Method: This research method was descriptive quantitative. The variable of this study was immunization coverage in Pedukuhan Sembuh Wetan Sidokarto Godean. The population in on this study was mothers with toddlers in Pedukuhan Sembuh Wetan Sidokarto Godean (amount 48 mother). Samples were taken by total sampling technique.Result: There was a child 0-12 months old (2.08%) who have not received BCG immunization from 47 toddler (97.92%). Polio immunization (polio 1 and 2) have reached target UCI was 97.92% and 93.76%. For polio 3 and 4, the overall immunization coverage has not reached the target of 85.43% and 87.51%. DPT immunization coverage has not reached the target (89.59%). HepB coverage was below of 80%. For measles immunization coverage has reached until 100%.Conclusion: Coverage of polio vaccination (3 and 4), DPT, and HepB has not reached 90% of Universal Child Immunization (UCI) target status. Coverage of BCG vaccination and measles has reached 90% of Universal Child Immunization (UCI) target status.Keywords: immunization coverage, toddler